POLLEN MORPHOLOGY OF SOME SELECTED BEE FLORAL RESOURCES OF Apis cerana F. AND Apis mellifera L. USING SCANNING ELECTRON MICROSCOPY FROM HIMACHAL PRADESH, INDIA - JAMWAL, RADHIKA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Pollen morphology of ten nectariferous and polleniferous bee floral resources of honeybees Apis cerana F. (Asian honeybee) and Apis mellifera L. (European honeybee) was studied by using scanning electron microscope. Pollen grains of Foeniculum vulgare, Taraxacum officinale, Jacaranda mimosifolia, Sechium edule, Emblica officinalis, Ocimum sanctum, Lagerstroemia indica, Cedrela toona, Eucalyptus tereticornis and Moringa oleifera belonging to different bee favored families were examined for the morphological characterization. The pollen grains were analyzed for aggregation, shape, shape class, size, aperture, polarity, symmetry and exine ornamentation. All the pollens observed in the study had solitary grains, isopolar and have radial symmetry. The shape and shape class of pollen grains varies among different families. The size of pollen grains studied ranged from small, medium to large sized among different plant families. Most of pollens observed were 3-colporate, except pollens of Sechium edule which were 9-colpate, Emblica officinalis and Lagerstroemia indica were 3-4-zonocolporate, Ocimum sanctum were 6-colpate, Cedrela toona and Moringa oleifera were 3- zonocolporate. Variation was also observed in surface pattern of different pollens belonging to different families.